The Role of Host Genetic Factors in Coronavirus Susceptibility: Review of Animal and Systematic Review of Human Literature - LoPresti, Marissa; Beck, David B.; Duggal, Priya; Cummings, Derek A.T.; Solomon, Benjamin D. (American journal of human genetics, 2020)
The SARS-CoV-2 pandemic raises many scientific and clinical questions. These include how host genetic factors affect disease susceptibility and pathogenesis. New work is emerging related to SARS-CoV-2; previous work has been conducted on other coronaviruses that affect different species. We reviewed the literature on host genetic factors related to coronaviruses, systematically focusing on human studies. We identified 1,832 articles of potential relevance. Seventy-five involved human host genetic factors, 36 of which involved analysis of specific genes or loci; aside from one meta-analysis, all were candidate-driven studies, typically investigating small numbers of research subjects and loci. Three additional case reports were described. Multiple significant loci were identified, including 16 related to susceptibility (seven of which identified protective alleles) and 16 related to outcomes (three of which identified protective alleles). The types of cases and controls used varied considerably; four studies used traditional replication/validation cohorts. Among other studies, 30 involved both human and non-human host genetic factors related to coronavirus, 178 involved study of non-human (animal) host genetic factors related to coronavirus, and 984 involved study of non-genetic host factors related to coronavirus, including involving immunopathogenesis. Previous human studies have been limited by issues that may be less impactful now, including low numbers of eligible participants and limited availability of advanced genomic methods; however, these may raise additional considerations. We outline key genes and loci from animal and human host genetic studies that may bear investigation in the study of COVID-19. We also discuss how previous studies may direct current lines of inquiry. The SARS-CoV-2 pandemic raises many scientific and clinical questions. These include how host genetic factors affect disease susceptibility and pathogenesis. New work is emerging related to SARS-CoV-2; previous work has been conducted on other coronaviruses that affect different species. We reviewed the literature on host genetic factors related to coronaviruses, systematically focusing on human studies. We identified 1,832 articles of potential relevance. Seventy-five involved human host genetic factors, 36 of which involved analysis of specific genes or loci; aside from one meta-analysis, all were candidate-driven studies, typically investigating small numbers of research subjects and loci. Three additional case reports were described. Multiple significant loci were identified, including 16 related to susceptibility (seven of which identified protective alleles) and 16 related to outcomes (three of which identified protective alleles). The types of cases and controls used varied considerably; four studies used traditional replication/validation cohorts. Among other studies, 30 involved both human and non-human host genetic factors related to coronavirus, 178 involved study of non-human (animal) host genetic factors related to coronavirus, and 984 involved study of non-genetic host factors related to coronavirus, including involving immunopathogenesis. Previous human studies have been limited by issues that may be less impactful now, including low numbers of eligible participants and limited availability of advanced genomic methods; however, these may raise additional considerations. We outline key genes and loci from animal and human host genetic studies that may bear investigation in the study of COVID-19. We also discuss how previous studies may direct current lines of inquiry.